ICT and Productivity Growth Within Value Chains - Chuan Liu; Marianne Saam (Review of Income and Wealth, 2022)
Growth accounting has documented an important contribution of information and communication technology (ICT) capital deepening to sectoral labor productivity growth during the late 1990s, especially for the knowledge-intensive services that are used to an important extent as intermediate inputs to other sectors. Our approach traces labor productivity growth not within sectors but within value chains of final products. A main result is that more than half of the productivity gains related to ICT capital deepening for manufactured goods are contributed by upstream industries, mostly by knowledge-intensive services. For a number of countries, similar magnitudes of upstream contributions of ICT capital deepening are observed for ICT products and for services that are not knowledge-intensive. The major part of these contributions is domestic rather than foreign. Moreover, the high sectoral growth in total factor productivity (TFP) in the ICT sector contributes only moderately to effective TFP growth in non-ICT value chains.
Keywords: 330; ICT; economic growth; productivity; value chains; growth accounting